HUMAN CAPITAL ANALYTICS AND DECISION MAKING - Zaenal Aripin; Adang Haryaman; Maya Ariyanti (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2025)
Amid rapid digital transformation, the impact of the COVID-19 pandemic, and increasing sustainability demands from stakeholders, organizations face complex challenges in optimizing human capital to achieve sustainable competitive advantage. Conventional approaches are often no longer sufficient. Therefore, human capital analytics has become an essential instrument in supporting data-driven decision-making, strengthening organizational agility, fostering innovation, and enhancing cross-functional collaboration (Davis & Kumar, 2024; Buchory et al., 2024). This study aims to investigate the role of HR analytics in strategic decision-making, identify the drivers of transformation and implementation barriers, and analyze their implications for various organizational performance outcomes. This research employs a mixed-methods design with two primary approaches. First, a quantitative survey was conducted involving 312 senior managers in Southeast Asia (response rate 26%) between January and September 2024, using 87 validated Likert-scale items. Second, qualitative case studies were carried out in 28 cross-sector organizations through 94 semi-structured interviews (average duration 75 minutes), direct observations, and document analysis. Data analysis was performed using multivariate techniques, including regression and correlation (e.g., r = 0.67 for the communication variable), as well as thematic coding to ensure triangulation of findings. The findings indicate that 78% of organizations initiated transformation within the last three years, primarily driven by competitive pressures (72%) and technological advancements (68%). A phased transformation approach supported by change management practices—with a budget allocation of 15–20%—achieved success rates of 71–83%. The impacts include a 34% increase in efficiency (range 18–67%), a 28% rise in customer satisfaction, a 22% improvement in employee engagement, and an 18% growth in financial margins. The primary barrier, organizational resistance (68%), was effectively mitigated through early stakeholder involvement (+140%) and intensive training programs (+165%). This study contributes by developing an evidence-based framework to strengthen HR analytics capabilities, providing actionable insights for HR practitioners, organizational leaders, and policymakers in the VUCA context of Southeast Asia, and offering recommendations for future research agendas, including longitudinal studies to examine the sustainability of transformation impacts.